The Role of International Organization for Migration in Handling Human Trafficking in Sambas Regency, West Kalimantan Province - Nugrahaningsih, Nurfitri; Alunaza, Hardi; Lutfie, Ratu Zahirah (Universitas Muhammadiyah Yogyakarta, 2020)
Human trafficking becomes a central issue in the globalization era for being an epidemic in various countries. Cases of human trafficking have been rife for a long time in Indonesia, even in some areas such as East Nusa Tenggara, East Kalimantan, West Nusa Tenggara, and West Kalimantan, this phenomenon is vulnerable. West Kalimantan Province has ranked second highest in human trafficking cases in Indonesia, particularly in Sambas Regency, an area directly adjacent to Malaysia. This paper aimed to describe the role of IOM in tackling human trafficking cases in Sambas Regency, West Kalimantan. This study utilized a qualitative approach with descriptive writing patterns, and data sources were based on literature review and field studies through interviews with IOM and the local government of Sambas Regency. International organizations and institutional liberalism theories were employed to analyze the phenomenon. The results revealed that IOM performed its role and function by cooperating with the local government in conducting socialization and involving the government both vertically and horizontally. IOM also conducted reintegration and victim assistance. Moreover, IOM carried out discovery processes in economic and social terms. The existence of IOM can be the right partner for the government in dealing with human trafficking. Thereby, cooperation and support for the implementation of government policies can be established.